Perilaku Prososial Dan Unit-Unit Kegiatan Mahasiswa - Farid, Muhammad (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract.  This research aims to determine whether there are differences in prosocial behavior of students who are active in student activities unit art, Islamic spirituality and nature lovers and whether there are differences in prosocial behavior of male and female students at the University of 45 Surabaya. From the the 90 respondents, consisting of 45 male and 45 female, it is obtained the following result : The mean of prosocial behavior does not differ between students who are active in student activities unit art, Islamic spirituality and nature lovers (p > 0,05, not significant), the hypothesis is not accepted. The mean of prosocial behavior of students does not differ between those who are active in unit activities of Islamic spirituality and art, the mean of prosocial behavior of students who are active in unit activities of art and nature lovers are not different. Similarly, there is no difference in the mean of prosocial behavior of students who are active in unit activities of Islamic spirituality and nature lovers (p > 0,05, not significant). Hypothesis is not accepted. The other result shows that the mean of prosocial behavior looks very significant differences between male and female students (p < 0,01, not significant). Hypothesis is accepted. Mean of prosocial on female students’ behavior is higher than the mean of pro-social behavior of male students.Key words :   Prosocial behavior, student activities